2021
DOI: 10.3346/jkms.2021.36.e207
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric and Altmetric Analyses of Publication Activity in the Field of Behcet's Disease in 2010–2019

Abstract: Background Behcet's disease (BD) is a systemic vasculitis accompanied by oral-genital ulcers, ocular, cerebral, and gastrointestinal disorders. The aim of this study was to evaluate BD articles published between 2010–2019 bibliometrically and to provide up-to-date data. A secondary aim was to present a different perspective using altmetric assessments. Methods This bibliometric and altmetric research was performed with data obtained from the Web of Science database. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…In the bibliometric study conducted on Behçet, another disease with geographical distribution, it was revealed that Turkey is the dominant country in terms of the number of articles. Consistent with our results, Japan and Italy ranked in the top five [27]. In another FMF-related 1 3…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the bibliometric study conducted on Behçet, another disease with geographical distribution, it was revealed that Turkey is the dominant country in terms of the number of articles. Consistent with our results, Japan and Italy ranked in the top five [27]. In another FMF-related 1 3…”
Section: Discussionsupporting
confidence: 90%
“…The five journals that published the most articles in the field of FMF were Rheumatol Int, Clin Rheumatol, Clin Exp Rheumatol, Ann Rheum Dis and Pediatric Rheumatol, respectively. In the bibliometric study on Behçet disease, Clin Exp Rheumatol (first place), Clin Rheumatol (second place) and Rheumatol Int (fourth place) were among the top five journals [27]. Considering the age group in which FMF emerges, it is an expected result for a pediatric journal to be in the top five.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of BD is high in the Mediterranean coast, the Middle East, and Southeast Asia, namely the "Silk Road" region, and low in Europe and America. The prevalence of BD in China is 14.0/100,000, which is very similar to that in Japan (13.5/100,000) [2]. However, the pathogenesis of BD is not clear, and previous studies have shown that the incidence of BD is mainly related to autoimmune, environmental, and genetic factors [3].…”
Section: Introductionmentioning
confidence: 64%
“…The purple outer ring reflects a node with a centrality greater than 0.1, which indicates that it has a significant impact [ 32 ]. The resulting data were analyzed using Microsoft 365 Excel and IBM SPSS Grad Pack v27 [ 33 ]. A p -value of <0.05 was considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%